A New Combination of Substrates: Biogas Production and Diversity of the Methanogenic Microorganisms - Kushkevych, Ivan; Vítězová, Monika; Vítěz, Tomáš; Kováč, Jozef; Kaucká, Petra; Jesionek, Wojciech; Bartoš, Milan; Barton, Larry (Open life sciences, 2018)
Agriculture, food industry, and manufacturing are just some of the areas where anaerobic technology can be used. Currently, anaerobic technologies are mainly used for wastewater treatment, solid waste treatment, or for the production of electrical and thermal energy from energy crops processing. However, a clear trend is towards more intensive use of this technology in biomass and biodegradable waste processing and hydrogen or biomethane production. An enormous number of anaerobic digesters are operating worldwide but there is very little information about the effect of different substrate combinations on the methanogens community. This is due to the fact that each of the anaerobic digesters has its own unique microbial community. For the most effective management of anaerobic processes it would be important to know the composition of a consortium of anaerobic microorganisms present in anaerobic digesters processing different input combinations of raw material. This paper characterizes the effect of the input raw materials on the diversity of the methanogen community. Two predominant microorganisms in anaerobic digesters were found to be 99% identity by the sequences of the 16S rRNA gene to the Methanoculleus and Thermogymnomonas genera deposited in GenBank.
Keywords: biogas; Archaea; methanogenic microorganisms; anaerobic digesters; methane production